Pengembangan Multimedia Fisika Berbasis Problem Based Learning Untuk Meningkatkan Pemecahan Masalah Peserta Didik - Muhammad Ari Kusumawadi; Muhammad Zuhdi; Wahyudi Wahyudi (Indonesian Journal of Applied Science and Technology, 2020)
The process of learning physics still uses conventional methods and does not yet use various media. This also affects the learning outcomes of students who are low. The low learning outcomes show low problem-solving abilities. So that one media needs to be developed, one of them is physics-based on problem-based learning. This study aims to determine the feasibility and reliability of multimedia physics based on problem-based learning to improve problem-solving skills. This research is a type of research development (Research and Development). This study's model uses the 4-D model, which consists of the defining, designing, developing, and disseminating stages. The research phase is limited to the development stage. The data collection technique uses a questionnaire. Data were analyzed by finding the percentage of eligibility and reliability. The results obtained that multimedia physics and learning tools are suitable because the percentage is between 76% -100% and reliable because the percentage is above 75%.  So, it can be concluded that multimedia physics is worthy of being tested on high school students in class XI.